METHODOLOGY OF DEVELOPING STRENGTH ENDURANCE OF SECONDARY SCHOOL CHILDREN - Khasanov, Dilmurod (Журнал иностранных языков и лингвистики, 2023)
This article presents a scientific exploration of strategies to develop strength endurance in secondary school children. The study aims to provide a comprehensive understanding of the factors influencing strength endurance development, along with practical interventions and recommendations for educators and PE teachers. Strength endurance plays a crucial role in the physical development and overall well-being of secondary school children. It enables them to perform everyday tasks with ease and enhances their performance in sports and other physical activities. This article aims to explore the importance of developing strength endurance among secondary school children and provides an overview of effective strategies that can be employed to achieve this goal.